Subjective benefits from wearing self-fitting over-the-counter hearing aids in the real world - Sheng, Tong; Pasquesi, Lauren; Gilligan, Jennifer; Chen, Xing-Jie; Swaminathan, Jayaganesh (Frontiers in Neuroscience, 2024)
Introduction In 2022, the US Food and Drug Administration enacted final regulations to establish the category of over-the-counter (OTC) hearing aids aimed at reducing barriers to access hearing health care for individuals with self-perceived mild to moderate hearing loss. However, given the infancy of this device category, the effectiveness of OTC hearing aids in real-world environments is not yet well understood. Methods and results To gain insights into the perceived benefit of self-fitting OTC hearing aids, a two-pronged investigation was conducted. In the primary investigation, 255 active users of a self-fitting OTC hearing aid were surveyed on their perceived benefit using an abridged form of the Satisfaction with Amplification in Daily Living (SADL) scale. The mean global (4.9) and subscale scores (Positive Effect (PE): 4.3; Negative Features (NF): 4.3; Personal Image (PI): 6.1) were within the range of those previously reported for users of prescription hearing aids. In the secondary investigation, 29 individuals with self-reported hearing impairment but no prior experience with the investigational self-fitting OTC hearing aids used the devices and reported their perceived benefit and satisfaction following short-term usage. For this prospective group, the global SADL (5.4) and subscale scores (PE: 4.8; NF: 4.9; PI: 6.5) following a minimum of 10 weeks of real-world use were also within the range of those previously reported for traditional hearing aid users. In addition, this prospective group was also asked quality of life questions which assessed psychological benefits of hearing aid use. Responses to these items suggest hearing aid related improvements in several areas spanning emotional health, relationships at home and at work, social life, participation in group activities, confidence and feelings about one’s self, ability to communicate effectively, and romance. Discussion Converging data from these investigations suggest that self-fitting OTC hearing aids can potentially provide their intended users with a level of subjective benefit comparable to what prescription hearing aid users might experience.